Dietary intake and eating behavior in depot medroxyprogesterone acetate users: a systematic review - Silva,P. (2018)
Because of weight gain, women often discontinue hormonal contraception, especially depot medroxyprogesterone acetate (DMPA). Our objective was to conduct a systematic review of studies describing dietary intake or eating behavior in DMPA users to understand whether the use of DMPA is associated with changes in dietary habits and behaviors leading to weight gain. We searched the PubMed, POPLINE, CENTRAL Cochrane, Web of Science, and EMBASE databases for reports published in English between 1980 and 2017 examining dietary intake or eating behavior in healthy women in reproductive age and adolescents using DMPA (150 mg/mL). Of the 749 publications screened, we excluded 742 due to duplicates (96), not addressing the key research question (638), not reporting dietary intake data (4), and not evaluating the relationship of body weight and dietary or eating behaviors (4). We identified seven relevant studies, including one randomized placebo-controlled trial, one non-randomized paired clinical trial, and five cohort studies. The randomized trial found no association and the other reports were inconsistent. Findings varied from no change in dietary intake or eating behavior with DMPA use to increased appetite in the first six months of DMPA use. Few studies report dietary intake and eating behavior in DMPA users and the available data are insufficient to conclude whether DMPA use is associated with changes in dietary habits or behavior leading to weight gain.